2016
DOI: 10.1080/21645515.2016.1141158
|View full text |Cite
|
Sign up to set email alerts
|

Tempest in a teapot: A systematic review of HPV vaccination and risk compensation research

Abstract: There has been some concern among parents and in the media that vaccinating children against human papillomavirus could be seen as giving children permission to engage in risky sexual behaviors (also known as sexual disinhibition). Several studies have found this concern to be unfounded but there have been no attempts to synthesize the relevant studies in order to assess if there is evidence of sexual disinhibition. The aim of this study was to synthesize recent literature examining sexual behaviors and biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
66
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 52 publications
5
66
1
Order By: Relevance
“…A decade since the licensure of the first HPV vaccine, its population-level effects look very promising, both in terms of efficiency 23 and safety. 24 Adding to this picture, the current review 20 shows that a considerable number of studies find no indication that HPV vaccination leads to sexual risk compensation, hence such concerns seem unwarranted.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…A decade since the licensure of the first HPV vaccine, its population-level effects look very promising, both in terms of efficiency 23 and safety. 24 Adding to this picture, the current review 20 shows that a considerable number of studies find no indication that HPV vaccination leads to sexual risk compensation, hence such concerns seem unwarranted.…”
mentioning
confidence: 92%
“…Although 20 studies all point in the same direction, 20 there are still some issues left to address. First, more large-scale longitudinal studies are needed.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…27,29,30 A ban of the HPV vaccine in some Catholic schools 31 may have suggested that receiving the HPV vaccine contributes to sexual disinhibition and related adverse outcomes (e.g., younger age at first intercourse, increased number of sexual partners and reduced use of contraception). 27,32 However, little evidence has been produced to substantiate these claims, 33 and Canadian parents rarely report these reasons as barriers to vaccination. 28 The media also contributes to influencing public opinion, and a number of sensational articles on the HPV vaccine have been published in Canadian media (e.g., a Toronto Star article that has since been retracted).…”
Section: Misconceptionsmentioning
confidence: 99%